Habitat characteristics and distribution patterns of blood cockle Anadara antiquata (Linnaeus, 1758) in the Waters of Senggarang Besar, Tanjungpinang City - Sartika, Melliani; Susiana, Susiana; Zahid, Ahmad (Akuatikisle: Jurnal Akuakultur, Pesisir dan Pulau-Pulau Kecil, 2025)
This study aims to identify the habitat characteristics and distribution patterns of the antique ark Anadara antiquata in the waters of Senggarang Besar, Tanjungpinang City. The research was conducted from July to September 2024. The research process included site surveys, field data collection, sample analysis, data processing, data analysis, and preparation of the final report. Sampling points were determined using purposive sampling at three observation stations. Antique ark samples were collected using the sweep area method at each station, with an observed area of 10 x 10 meters. The results showed that antique ark in Senggarang Besar prefer habitats with high organic content, relatively lower water temperatures within the optimal range (around 29.83°C), stable salinity (around 30 ppt), and low but still safe levels of dissolved oxygen (around 5.17 mg/L), with these characteristics being most evident at Station I. The distribution pattern analysis showed that all stations had an index of dispersion (Ip) value greater than 0.5, indicating a clumped distribution pattern of the antique ark population in the study area.